2022
DOI: 10.1051/0004-6361/202142512
|View full text |Cite
|
Sign up to set email alerts
|

HI-H2 transition: Exploring the role of the magnetic field

Abstract: Context. Atomic gas in the diffuse interstellar medium (ISM) is organized in filamentary structures. These structures usually host cold and dense molecular clumps. The Galactic magnetic field is considered to play an important role in the formation of these clumps. Aims. Our goal is to explore the role of the magnetic field in the H i-H 2 transition process. Methods. We targeted a diffuse ISM filamentary cloud toward the Ursa Major cirrus where gas transitions from atomic to molecular. We probed the magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 121 publications
2
14
1
Order By: Relevance
“…Using PanSTARRS photometry, Schlafly et al (2014) found a much larger distance of about 350 ± 25 pc for the Ursa Major MBM 30 cloud, placing it at about the same distance as Polaris. Using the 3D dust extinction map by Green et al (2018), Tritsis et al (2019 found a distance of about 300 pc toward the western part of the Ursa Major complex, consistent with recent polarimetric data presented in Skalidis et al (2022) In this work, we find that complexes in the NCPL, as well as the diffuse material that surrounds them, have distances varying from about 310 to 450 pc (Section 3).…”
Section: Distancesupporting
confidence: 90%
See 4 more Smart Citations
“…Using PanSTARRS photometry, Schlafly et al (2014) found a much larger distance of about 350 ± 25 pc for the Ursa Major MBM 30 cloud, placing it at about the same distance as Polaris. Using the 3D dust extinction map by Green et al (2018), Tritsis et al (2019 found a distance of about 300 pc toward the western part of the Ursa Major complex, consistent with recent polarimetric data presented in Skalidis et al (2022) In this work, we find that complexes in the NCPL, as well as the diffuse material that surrounds them, have distances varying from about 310 to 450 pc (Section 3).…”
Section: Distancesupporting
confidence: 90%
“…In a gaseous disk affected by supernovae at a rate on the order of 1 per 50 yr galaxy wide, interconnected cavities and tunnels are expected from the growth of clusters and chains of connected supernova remnants (Cox & Smith 1974). Cox & Smith (1974) predicted that the resulting tunnel network would have low density, high temperature, and a very low magnetic field strength; the field properties seem consistent with the minimum of emission at 408 MHz inside the cavity (M91) and the enhancement of the magnetic field strength in complexes along the loop (Heiles 1989;Myers et al 1995;Pound & Goodman 1997;Tritsis et al 2019;Skalidis et al 2022).…”
Section: Origin Of the Ncplmentioning
confidence: 95%
See 3 more Smart Citations